Exergoeconomic Analysis of Integrated Rice Mill Systems with Gasifiers - Omil Charmyn Chatib; I Wayan Budiastra; Mohamad Solahudin; Y. Aris Purwanto; Leopold Oscar Nelwan (Jurnal Keteknikan Pertanian, 2023)
Applying the concept of utilizing rice mill waste as an energy source can support the increase in the productivity of renewable energy. The exergonomic concept can be used as one of the steps to see opportunities for husks to be used as an energy booster in a rice mill system that has been integrated with a gasifier. Specific Exergy Cost (SPECO) is used as the method, that combines exergy and economic analysis by applying the cost concept to the thermal system. Based on the analysis results, gas producers can replace diesel fuel in small-sized rice mill systems. Compared with these inputs, husks and energy products from the gasifier can produce nearly 6 and 4 times the exergy, respectively. In addition, gas utilization producers can also reduce fuel expenditure costs by up to 84.67%.